Establishing Backward Causation on Empirical Grounds: An Interventionist Approach. (21st May 2019) - Gebharter, Alexander; Graemer, Dennis; Scheffels, Frenzis H.
Abstract : We propose an analysis of backward causation in terms of interventionism that can avoid several problems typically associated with backward causation. Its main advantage over other accounts is that it allows for reducing the problematic task of supporting backward causal claims to the unproblematic task of finding evidence for several ordinary forward directed causal hypotheses.